2015
DOI: 10.5812/ircmj.11420
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Weight and Female Sexual Dysfunction: A Case Control Study

Abstract: Background:About 79% of the pregnant women experience sleep disorders and 70% of pregnant women experience some symptoms of the depression. Physiologic, hormonal, and physical changes of pregnancy can predispose mothers to depression these disorders before, during, and after childbirth and might be aggravated by neglecting health behavior. Health behavior education might be useful for the management of depression in pregnant women.Objectives:This study aimed to evaluate the effect of sleep health behavioral ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Among Portuguese women, greater frequency of orgasms from PVI without clitoral masturbation was related to a slimmer waist (Costa & Brody, 2014). In congruence with these findings, female sexual dysfunctions and sexual dissatisfaction have been shown to be cross-culturally related to body fat indices (Brody & Weiss, 2013;Castellini et al, 2010;Esposito et al, 2007;Morotti et al, 2013;Mozafari et al, 2015;Veronelli et al, 2009;Yaylali, Tekekoglu, & Akin, 2010). In congruence with these findings, female sexual dysfunctions and sexual dissatisfaction have been shown to be cross-culturally related to body fat indices (Brody & Weiss, 2013;Castellini et al, 2010;Esposito et al, 2007;Morotti et al, 2013;Mozafari et al, 2015;Veronelli et al, 2009;Yaylali, Tekekoglu, & Akin, 2010).…”
Section: Please Scroll Down For Articlementioning
confidence: 52%
“…Among Portuguese women, greater frequency of orgasms from PVI without clitoral masturbation was related to a slimmer waist (Costa & Brody, 2014). In congruence with these findings, female sexual dysfunctions and sexual dissatisfaction have been shown to be cross-culturally related to body fat indices (Brody & Weiss, 2013;Castellini et al, 2010;Esposito et al, 2007;Morotti et al, 2013;Mozafari et al, 2015;Veronelli et al, 2009;Yaylali, Tekekoglu, & Akin, 2010). In congruence with these findings, female sexual dysfunctions and sexual dissatisfaction have been shown to be cross-culturally related to body fat indices (Brody & Weiss, 2013;Castellini et al, 2010;Esposito et al, 2007;Morotti et al, 2013;Mozafari et al, 2015;Veronelli et al, 2009;Yaylali, Tekekoglu, & Akin, 2010).…”
Section: Please Scroll Down For Articlementioning
confidence: 52%
“…The PSQI was finally designed by Buysse et al (1989) with a sensitivity of 89.6%, specificity of 86.5%, validity of 88% (r = 0.88) and reliability of 83%. Its validity and reliability were confirmed by research in other countries and in Iran (Buysse et al, 1989;Rezaei et al, 2015;Zahra and Elham, 2014).…”
Section: Methodsmentioning
confidence: 70%
“…In Jamali's study, a sig-nificant relationship was found between sexual function and age (P = 0.02), education level (P < 0.001), and occupation (P < 0.001) (16). Also, the results of Mozafari et al (20) showed age had a significant correlation with FSFI (P < 0.001) (22).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, sexual desire, arousal, lubrication, orgasm, satisfaction, and pain were statistically significant in both groups. Rada et al (22) found that obese persons in comparison to normal weight ones reported the lack of desire and sexual pleasure, abstention, and difficulties in sexual contact accomplishment. In Jamali et al's study (16), the most common sexual problems in infertile females decreased libido (95.2%) and anorgasmia (94.6%).…”
Section: Discussionmentioning
confidence: 99%